Teknik Dasar Lempar Cakram Mahasiswi Angkatan 2014 - Ahmad Atiq (Jurnal Visi Ilmu Pendidikan, 2015)
Discus throwing is one of the throwing events in athletics, where the tools were cast in the form of discs with a certain weight and size. Number discus throwing is always competed in every championship multy special event or championship for athletics, both for the individual as well as a mixture of boys and girls (Dasa Competition) for example, the official championships such as PON, SEA Games, Asian Games, Olympics etc. Sports discus throwing is one of the main numbers throwing competitions in athletics. However, in the indoor athletics, discus throwing numbers not raced. This sport has been around since the ancient Olympic Games. In discus throwing competition, athletes compete throwing a disc-shaped object as far as possible to follow the regulations. In the race's official athletics, each athlete was given the opportunity to throw as much as three times. Then, from a number of athletes at the beginning baba, will be selected eight best athletes, who will be given the opportunity three times to roll again. Discus throwing athletes raced for both men and women's health physical education and recreation, amounting to 25 student with good category 10 students with a percentage of 40% and categories were 8 students with a percentage of 32% and less than 7 student categories by percentage of 28% for the necessary kontiyu do exercises that basic throwing techniques in particular can be a better daughter. Keywords : basic techniques of throwing students of 2014  Abstrak:Lempar cakram adalah salah satu nomor lempar dalam cabang olahraga atletik, dimana alat yang dilemparkan berupa cakram dengan berat dan ukuran tertentu. Nomor lempar cakram ini selalu dilombakan dalam setiap kejuaraan multy event atau kejuaraan yang khusus untuk cabang olahraga atletik, baik untuk nomor perorangan putra dan putri maupun campuran (Dasa Lomba) misalnya, kejuaraan resmi seperti PON, Sea Games, ASEAN Games, Olimpiade dll. Olahraga lempar cakram adalah salah satu nomor perlombaan lempar yang utama dalam atletik. Namun, dalam perlombaan atletik indoor, nomor lempar cakram tidak diperlombakan. Olahraga ini telah ada sejak Olimpiade kuno. Dalam perlombaan lempar cakram, atlet berlomba melemparkan objek berbentuk cakram sejauh mungkin dengan mengikuti peraturan yang berlaku. Dalam perlombaan atletik resmi, setiap atlet diberi kesempatan melempar sebanyak tiga kali. Kemudian, dari sejumlah atlet pada baba awal, akan dipilih delapan atlet terbaik, yang akan diberi kesempatan tiga kali lemparan lagi.  Lempar cakram diperlombakan bagi atlet-atlet laki-laki ataupun perempuan pendidikan jasmani kesehatan dan rekreasi yang berjumlah 25 mahasiswi dengan kategori baik 10 mahasiswa dengan persentasi 40% dan kategori sedang 8 mahasiswa dengan persentasi 32% dan kategori kurang 7 mahasiswi dengan persentasi 28 % untuk perlu dilakukan latihan yang kontiyu agar tehnik dasar lempar cakram khususnya putri bisa bisa lebih baik. Kata Kunci : tehnik dasar lempar cakram mahasiswi angkatan 2014